2018
DOI: 10.3390/v10060299
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 19 Highly Conserved Vibrio cholerae Bacteriophages Isolated from Environmental and Patient Sources Over a Twelve-Year Period

Abstract: The Vibrio cholerae biotype “El Tor” is responsible for all of the current epidemic and endemic cholera outbreaks worldwide. These outbreaks are clonal, and it is hypothesized that they originate from the coastal areas near the Bay of Bengal, where the lytic bacteriophage ICP1 (International Centre for Diarrhoeal Disease Research, Bangladesh cholera phage 1) specifically preys upon these pathogenic outbreak strains. ICP1 has also been the dominant bacteriophage found in cholera patient stools since 2001. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Once we examined ICP1's effect on V. cholerae transcription, we next sought to document ICP1's transcriptional program. ICP1 has an approximately 126-kb genome and more than 200 predicted open reading frames (46). Less than one-quarter of ICP1's putative coding sequences have activities or functions that can be predicted through bioinformatic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Once we examined ICP1's effect on V. cholerae transcription, we next sought to document ICP1's transcriptional program. ICP1 has an approximately 126-kb genome and more than 200 predicted open reading frames (46). Less than one-quarter of ICP1's putative coding sequences have activities or functions that can be predicted through bioinformatic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We isolated eight new ICP1 isolates from cholera patient stool samples collected between 2015 and 2017 and found that all isolates harbour CRISPR-Cas. Thus, it appears that ICP1 isolates lacking CRISPR have not been identified in Bangladesh since 2006 [23]. Analysis of the CRISPR arrays indicates a strong selection for spacers specifically targeting PLE (figure 1 b ; electronic supplementary material, table S5), supporting the function of the ICP1-encoded CRISPR-Cas system as a counter-attack against the anti-phage island PLE [13].…”
Section: Resultsmentioning
confidence: 99%
“…Paired-end sequencing (2 × 150 bp) was performed on an Illumina HiSeq4000 (University of California, Berkeley QB3 Core Facility). Sequencing assembly/mapping and detection of CRISPR was performed as described [23]. The genome of the V. cholerae clinical isolate KS393 was sequenced on Illumina HiSeq4000, PacBio Sequel and Oxford Nanopore MinION sequencers (University of California, Berkeley QB3 Core Facility).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once we examined ICP1's effect on V. cholerae transcription, we next sought to document ICP1's transcriptional program. ICP1 has an approximately 126kb genome and more than 200 predicted open reading frames [42]. Less than a quarter of ICP1's putative coding sequences have activities or functions that can be predicted through bioinformatic analysis.…”
Section: Establishing the Icp1 Transcriptional Programmentioning
confidence: 99%